(untitled) (Bioresearch Communications, 2023)
Rationale: Urinary tract infections (UTI) occur more frequently in patients with type 2 diabetes. In developing countries, impairments in the defense system, metabolic disorder during diabetes, and incomplete bladder emptying all contribute to the pathogenesis of UTI in diabetic patients. This comparative study is undertaken to reveal the prevalence of uropathogens and their antimicrobial resistance patterns, and to assess hematological biomarker in diabetic and non-diabetic UTI patients. Methods: The prevalence of uropathogens were tested in 40 diabetic and 40 non-diabetic UTI patients. The antimicrobial susceptibility pattern of bacterial isolates were assessed by the Kirby-Buer disc-diffusion method. Moreover, the bacterial load, Gram-staining, biochemical and serological assays were performed using appropriate methods. Results: The findings showed that diabetic patients are more likely to UTI compared to non-diabetic patients. In terms of uropathogenic prevalence, 61% Escherichia coli, 34% Klebsiella pneumoniae, 2% Staphylococcus aureus, 2% Pseudomonas aureginosa and 1% others. The antimicrobial resistance profile demonstrated that most of the bacterial isolates were resistant to amoxicillin, ampicillin, erythromycin and methicillin but susceptible to azithromycin, chloramphenicol and ciprofloxacin. Moreover, the drug efflux pumps activity and bacterial burden were significantly high among antimicrobial resistant bacterial isolates. Besides, the C-reactive protein, Erythrocyte sedimentation rate, glycosylated hemoglobin A1C, neutrophils and lymphocytes were significantly high in diabetic UTI patients. Conclusion: This study found E. coli was the most frequent bacteria isolates, and this observation is consistent others. Diabetic UTI patients are more vulnerable with high bacterial burden and systemic inflammation. Bioresearch Commu. 10(1): 1413-1419, 2024 (January)